Limits On Freedom Of The Press In A Democratic State: Between The Press Law And The Ite Law - M. Riyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Freedom of the press constitutes one of the essential pillars of a democratic state governed by the rule of law, as it plays a crucial role in social oversight, information dissemination, the formation of public opinion, and political education of citizens. A free and responsible press is therefore a fundamental prerequisite for the realization of transparent and accountable governance. Nevertheless, press freedom cannot be interpreted as an absolute or unlimited right. Within constitutional practice, such freedom remains subject to legal restrictions intended to safeguard the public interest, maintain social order, and ensure respect for the rights and reputations of individuals. In Indonesia, guarantees of press freedom are specifically regulated under Law Number 40 of 1999 on the Press, which affirms the principles of press independence, media autonomy, and dispute resolution mechanisms through the right of reply and the role of the Press Council. However, rapid developments in information and communication technology have expanded journalistic activities into the digital sphere, causing press products to intersect with Law Number 11 of 2008 on Electronic Information and Transactions, as amended. This situation has given rise to a dual regulatory framework that frequently generates legal debate, particularly when journalistic works are alleged to violate criminal provisions under the EIT Law. The application of the EIT Law to press activities potentially creates normative conflicts and raises concerns regarding the criminalization of journalism, which may undermine freedom of expression. Accordingly, this article aims to examine the limits of press freedom within the framework of a democratic rule-of-law state and to analyze the relationship, distinctions, and potential normative conflicts between the Press Law and the EIT Law. This analysis is expected to offer an academic contribution toward formulating a model of press freedom regulation that is proportional, equitable, and consistent with democratic principles and the protection of human rights.